IMPROVING PROFESSIONAL AND LINGUISTIC COMPETENCE OF STUDENTS IN TECHNICAL UNIVERSITIES THROUGH RUSSIAN LANGUAGE INSTRUCTION BASED ON E-LEARNING TECHNOLOGIES (Web of Teachers: Inderscience Research, 2025)
The article examines the effectiveness of incorporating electronic dictionaries in Russian language classes for students from diverse national backgrounds in technical universities. The development of professional language competence plays a vital role in the holistic growth of individuals and enhances their competitiveness in the job market. The integration of electronic dictionaries during classes significantly streamlines the process of handling professional terms and unfamiliar vocabulary.